Circular economy in global firm: A system change perspective to closed loop thinking. - Wang, Huiyan (My University, 2022)
The study aims to investigate how does global firm utilise system change perspective to closed loop thinking for creating circular economy strategy in the energy industry. The study adopted 4 circular economy implementation strategies and 4 circular economy principles from relevant circular economy literature. The theoretical framework is empirically tested utilizing a qualitative single case study research methodology. The primary data was obtained by a purposive sampling technique. 3 semi-structured interviews and 2 webinars were utilised to obtain both primary and secondary data for the empirical analysis. The semi-structured interviews were obtained during the winter of 2022 from Project Manager, Technology Development Manager, and Senior Business Development Manager of the Power to X Project of Wärtsilä Energy Business unit. The overall empirical findings suggest that Wärtsilä recognises the Power to X project as an important reflection to its strategic vision for a carbon neutral smarter society. The empirical data analysis has identified that all the four implementation strategies and principles have been utilised in the Power to X project and especially cleaner production using renewable materials, and zero waste policy have been found to be most effective strategies. Whereas recycling and reduction principles found to be most prominent guiding circular economy principles. Based on the data analysis it is possible to argue that the Power to X project could be a catalyst of system change. The empirical analysis also reveals that Wärtsilä’s Power to X project has ensured implementation of different circular economy strategies by utilising certain measures. Furthermore, beyond the scope of the identified literature, this study contributes to the existing system change perspective literature by adding value co-creation and industry alliances as a new but effective circular economy implementation strategy. However, it is an unexpected empirical finding that recovery principle has no influence for the Power to X project. Based on the comprehensive literature review and empirical findings, the study proposes that system change perspective implementation strategies can assist global firms to achieve a certain principle of circular economy, such as Eco-design as a system change perspective strategy can help a global firm to achieve the circular economy principle of Reduction in its operations, and so forth.
Keywords: Circular economy, System change perspective, Closed loop thinking